Legume rhizodeposition promotes nitrogen fixation by soil microbiota under crop diversification - Qiao, Mengjie; Sun, Ruibo; Wang, Zixuan; Dumack, Kenneth; Xie, Xingguang; Dai, Chuanchao; Wang, Ertao; Zhou, Jizhong; Sun, Bo; Peng, Xinhua; Bonkowski, Michael; Chen, Yan (Nature communications, 2024)
Biological nitrogen fixation by free-living bacteria and rhizobial symbiosis with legumes plays a key role in sustainable crop production. Here, we study how different crop combinations influence the interaction between peanut plants and their rhizosphere microbiota via metabolite deposition and functional responses of free-living and symbiotic nitrogen-fixing bacteria. Based on a long-term (8 year) diversified cropping field experiment, we find that peanut co-cultured with maize and oilseed rape lead to specific changes in peanut rhizosphere metabolite profiles and bacterial functions and nodulation. Flavonoids and coumarins accumulate due to the activation of phenylpropanoid biosynthesis pathways in peanuts. These changes enhance the growth and nitrogen fixation activity of free-living bacterial isolates, and root nodulation by symbiotic Bradyrhizobium isolates. Peanut plant root metabolites interact with Bradyrhizobium isolates contributing to initiate nodulation. Our findings demonstrate that tailored intercropping could be used to improve soil nitrogen availability through changes in the rhizosphere microbiome and its functions. Sustainability in agriculture can be improved harnessing biological N 2 fixation in legumes. Here, the authors combine different crops with peanut plants finding that maize and oilseed rape are the most successful combinations which have potential to enhance rhizosphere microbiota N 2 fixation.